Relationship lending: Is it Incentives or hidden information? - Vinicius Carrasco; Jo\~ao M. P. de Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
Relationships are a valuable technology to produce loans. (Berger and Udell [1995], Petersen and Rajan [1994], Aoki and Dinç [2002]). While there are convincing theories in which relationships solve hidden action or hidden information problems, there is very little empirical corroboration of either theory. In this paper, we assess the empirically validity of these theories in the small firm credit market. While results suggest that relationships are more valuable for firms with worse incentive misaligment problems, more informationally opaque firms do not seem to extract more value from relationships. Contrary to what most empirical research on the value of relationships has assumed (but not tested), this indicates that relationships are, at very least, as important for aligning incentives as they are for solving hidden information problems.
Keywords: 330